2019
DOI: 10.1590/1809-4430-eng.agric.v39n2p191-197/2019
|View full text |Cite
|
Sign up to set email alerts
|

Vegetative Development and Growing Degree-Days of Tropical and Winter Forages

Abstract: One of the limitations to producing irrigated forages is setting suitable biometric parameters to establish the entrance of animals to grazing areas. Such parameters can be measured or even estimated. Estimates are advantageous for being practical and able to be used for grazing optimization. This study aimed to evaluate the correlation among growing degree-days (GDD), canopy height (CH), leaf area index (LAI), and number of cycle days (NCD) of Guinea grass (Panicum maximum cv. Mombaça) and Bermuda grass (Cyno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 23 publications
(30 reference statements)
1
7
0
Order By: Relevance
“…2c and 2d), with 31% less than the daily thermal sum in-season dry. Similar results were observed by [17], with GDD daily accumulations higher in the spring/summer to Guinea grass with 36% (6.6 GDD d -1 in the autumn/winter, and 10.2 GDD d -1 spring/summer).…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…2c and 2d), with 31% less than the daily thermal sum in-season dry. Similar results were observed by [17], with GDD daily accumulations higher in the spring/summer to Guinea grass with 36% (6.6 GDD d -1 in the autumn/winter, and 10.2 GDD d -1 spring/summer).…”
Section: Resultssupporting
confidence: 87%
“…2c and 2d), both periods, with values of a similar thermal sum around 290 GDD, the crop reached the cut point or grazing with Luminous Interception Index by maximum leaves (LI = 95%) [6,8,14]. [17], noticed the same resulting to Guinea and Bermuda grasses (Cynodon genus) and concluded that it is possible to obtain correlation among CH, LAI, and GDD.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…There is a low efficiency of forage production processes in several properties of the region. According to Siri-Prieto e al (2020), this happens, among other factors, when the management of harvest does not respect the forage plant physiology and when issues of photosynthetically active radiation propitiate the rise of temperature, thermochemical conversion (Siri-Prieto et al, 2020;Dos Santos et al, 2019;Sanches et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Management techniques, such as defoliation and fertilization, specific for forage cultivated in a region, considering the edaphoclimatic conditions, will enhance production on a property. Therefore, it is necessary to combine strategies of frequency, intensity, and defoliation to achieve production efficiency, and for replacement models of the nutrients exported (Sanches et al, 2019;Dos Santos, 2019).…”
Section: Introductionmentioning
confidence: 99%